Dinâmica populacional e amostragem sequencial de Tibraca limbativentris em arroz irrigado - Pasini, Mauricio Paulo Batistella (2016)
Rice (Oryza sativa L.) is one of the most cereal produced and consumed in the world. Tibraca limbativentris insect speciegenerate significant losses. The monitoring of insect pests is essential element based on the Integrated Insect Pest Management being prerequisite for decision making for suppressive actions and parameter estimates for the population density in rice fields. The study aimed to quantify the population flow of T. limbativentris between crops and host plants, to determine the influence of the diameter of the host plant and species on the T. limbativentris quiescent population, determine the effect of the host plant distance from the border on the T. limbativentris quiescent population, study the population dynamics of T. limbativentris between the environment and the area of cultivation; to establish a relationship between the characteristics of the cultivation area and the T. limbativentris population and to create sequential sampling plans for T. limbativentris. In Santa Maria, RS. Have been made to ratings in the surrounding cultivation areas and the cultivation areas generated sampling grid of 30m x 30min six areas. From the sowing have been made to seven evaluations for each field in an area of 1m2, corresponding to 200 rice plants. In these areas adults of the species were quantified and the sum data used for the analysis. The T. limbativentris population in the off season is high in the vicinity and absent in the areas of cultivation, while during the harvest this flow is reversed, the population is higher in the cultivation area and less than or absent in the vicinity of host plants. The diameter and the host plant species influence the T. limbativentris population. Plants with 0.10 meters and Andropogon bicornis species have smaller populations of bed bugs. The largest population of T. limbativentris during the off season in surrounding host plants is concentrated up to 45 meters from the border, and they disperse up to 150 meters from the border. The population of T. limbativentris has high spatial dependence. The infestation of T. limbativentris in growing areas and their population levels have strong dependence on the surrounding area. The cultivation area dimensions influence the dispersion and the density of T. limbativentris. In the off season the population of T. limbativentris aggregate remains in host plants. During the harvest in farming areas, the distribution pattern and the adjustment to the probabilistic models are influenced by the stage of development of culture and crop size.The sequential sampling plan proposed in this study resulted in a reduction in the number of sampling units required for decision-making for the T. limbativentris control.